Toward CFD Modeling of Slag Entrainment in Gas Stirred Ladles. Issue 12 (9th February 2015) - Huang, Ao; Harmuth, Harald; Doletschek, Marianne; Vollmann, Sandra; Feng, Xuezhi
Abstract : Simulation of slag entrainment has proven to be very challenging since multiscale phenomena occur. Particular complexities relate to the droplet size and the applied large eddy simulation approach that both necessitate meshing with rather small cell sizes. Therefore, a computational fluid dynamics (CFD) simulation for the entire spatial range, including the total ladle volume, is not possible. In this investigation, an optimized CFD model was developed on the analytical framework for the fluid dynamics of the oil (slag)–water (metal) system that allows modeling of the oil–water experiments. Additionally, an improved UDF‐code was developed to compute the size and the distribution of slag droplets. The simulation results agree well with the physical model experiments and can reveal critical purging conditions and droplet distributions that enable emulsification and slag/steel and refractory/slag mass transfer. Presented results indicate that the analytical framework set for identification of boundary conditions is a reasonable step toward the effective emulsification process analysis. Based on this framework, the CFD modeling becomes a reliable and predictive approach that can be conveniently extrapolated to investigate relevant phenomena in industrial systems. Abstract : In this work an optimized CFD model developed on the analytical framework for boundary conditions identification is applied for LES simulations of slag entrainment and agrees well with physical model experiments. It can be employed in CFD modeling of slag entrainment in gas stirred ladles with respect to predicting critical purging conditions, and further slag/steel and refractory/slag mass transfer.